Frequency of High Antimicrobial Susceptibility Carbapenemase Producing Enterobacteriaceae in Clinical Isolates of a Set of Population - Faisal Iqbal Afridi, Saeeda Baig, Aliya Irshad Sani, Qamar Jamal (Journal of Rawalpindi Medical College, 2022)
Objective: The objective of the study was to determine the frequency and antimicrobial susceptibility pattern of Carbapenem-Resistant Enterobacteriaceae among clinical isolates in Karachi, Pakistan. Materials and Methods: This observational study was conducted at Ziauddin University Hospital, Karachi, Pakistan, from January to December 2017. The consecutive clinical isolates of the Enterobacteriaceae were collected and analyzed, using established conventional microbiological techniques. Antimicrobial susceptibility testing and Carbapenem resistance were detected by the initial screen test using the CLSI method. Statistical analysis was performed by SPSS version 17. Results: The total of 2100 clinical isolates of Enterobacteriaceae attained during this study time period, were predominantly from female patients 1300/2100 (61.9%), while male patients were 800/2100 (38.1%). The femaleto-male ratio was 1.6:1. The overall frequency of CRE among isolates of Enterobacteriaceae was 136/2100 (6.5%). Within individual organism group Klebsiella species had highest 108/136 (79.41%) frequency, followed by E.coli 22 (18.38%) and Enterobacter species 03 (2.21%). All CRE isolates were sensitive to Colistin and Fosfomycin. No resistance was observed against Tigecycline among Carbapenem-resistant isolates of E. coli and Enterobacter species. Conclusion: Both Colistin and Fosfomycin antimicrobials can be considered empirical treatment options for CRE suspected infections. Better practices and changes in policy matters are required to improve the deteriorating situation of health care. Keywords: Antimicrobial Susceptibility, Carbapenem-Resistant Enterobacteriaceae, Klebsiella. Escherichia coli.